Stochastic impulsive processes on superposition of two renewal processes - Koroliuk, V.S.; Manca, R.; D'Amico, G. (Український математичний вісник, 2014)
Stochastic impulsive processes given by a sum of random variables on superposition of two renewal processes are considered on increasing time intervals. Algorithms of average, diffusion approximation and large deviation generators are realized in the series scheme with a small series parameter under suitable scalings.